2012
DOI: 10.4172/2155-9597.1000132
|View full text |Cite
|
Sign up to set email alerts
|

» Indexing and Archiving | More Bacteriology & Parasitology Journals Journal of Bacteriology & Parasitology Download Journal Flier JBP Editorial Board Scientific Associations Ann Albihn 2010- Governmental commission on climate change and infectious diseases 2009 Commission on climate change and animal inf. diseases to the governmental investigation on the handling of animal inf. diseases(Djursmittoutredningen), Agricult. Ministry 2007- 2010 The trend surveillance and analysis Group (omvärldsråd) at

Abstract: Laboratory case definition of leptospirosis is scarcely defined by a solid evaluation that determines cut-off values in the tests that are applied. This study describes the process of determining optimal cut-off titers of laboratory tests for leptospirosis for a valid case definition of leptospirosis. In this case the tests are the microscopic agglutination test (MAT) and an in-house IgM enzyme-linked immunosorbent assay (ELISA) both on single serum and paired samples using a positive culture as the reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…The study sample consisted of 19 samples that yielded a positive culture and 44 samples that were negative by culture. From all 19 patients who had a positive culture, leptospirosis was also confirmed by serology on paired samples, consistent with our case definition [17]. From eight of the 44 cases that scored as culture negatives, a follow up sample was received that showed negative results in the serodiagnosis.…”
Section: Methodssupporting
confidence: 62%
“…The study sample consisted of 19 samples that yielded a positive culture and 44 samples that were negative by culture. From all 19 patients who had a positive culture, leptospirosis was also confirmed by serology on paired samples, consistent with our case definition [17]. From eight of the 44 cases that scored as culture negatives, a follow up sample was received that showed negative results in the serodiagnosis.…”
Section: Methodssupporting
confidence: 62%
“…Whereas molecular tests, such as the polymerase chain reaction (PCR), that demonstrate the presence of the causative agent in a clinical sample mainly during the first 5 days after the onset of the disease (DPO), serological tests depend on the accumulation of detectable amounts of anti-Leptospira antibodies in the late acute to convalescent samples [74][75][76] . Rapid diagnostic tests should ideally be accurate, simple to use, relatively inexpensive, easy to interpret, stable under extreme conditions, require little or no processing, and give the results within 1-2 hours 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The rapid diagnosis is highly useful at the peripheral facilities and might be integral for early outbreak warning and useful for monitoring outbreaks if a rapid unusual accumulation of cases might provide an early alert, provided that specimens are collected, transported, and stored in an adequate manner 76 . This review, which included retrospective and prospective studies, had the following limitations: i) high heterogeneity found between studies; ii) use of selected samples and the choice of case definition may be a source of bias; and iii) it is a misunderstanding that rapid tests are easy and therefore do not require experience; iv) it may reflect population-related differences, such as past exposure to leptospirosis, exposure to environmental leptospires, or infection with other infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC reflects how good of the test to distinguish between patients with and without disease [14]. In the ROC curve analysis, it showed that the AUC for serum dilutions 1:80 and 1:160 were 0.953 (95% Confidence Interval, CI =0.928-0.978) and 0.927 (95% CI =0.896-0.958) respectively (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…The protocol of preparing antigen and coating plate was according to the protocol described by Goris et al . [14]. Briefly, the culture was grow in EMJH medium, killed by formalin (final concentration 0.2% v/v), heated in a boiling water bath for 30 min and centrifuged for 30 min at 10,000 g. The 100 μl supernatant was pipetted into the well and left to be evaporated.…”
Section: Methodsmentioning
confidence: 99%